The Role of BAZNAS in the Province of West Kalimantan in Managing Zakat for Persons with Disabilities (UIN Sunan Kudus, 2025)
This study analyzes the role of the National Zakat Agency (BAZNAS) of West Kalimantan Province in managing zakat for persons with disabilities and its relevance to the Sustainable Development Goals (SDGs) and the National Medium-Term Development Plan (RPJMN). Using a descriptive qualitative approach, data were collected through in-depth interviews and observation. Research participants included BAZNAS managers, persons with disabilities as mustahik, officials from the Social Rehabilitation Department, and community representatives. The findings show that BAZNAS West Kalimantan has not implemented zakat programs specifically targeting persons with disabilities, and distribution remains dominated by consumptive assistance and limited empowerment initiatives. Key challenges include the lack of accurate disability data, limited human resource capacity, and insufficient coordination with relevant stakeholders. Although zakat has the potential to enhance economic independence and social inclusion for persons with disabilities, its current impact remains limited. Therefore, a more structured and strategic approach is required, including strengthening data collection systems, improving institutional capacity, and enhancing collaboration between BAZNAS, local governments, and the private sector. Such efforts are essential to increase the effectiveness, inclusiveness, and sustainability of zakat programs for persons with disabilities in West Kalimantan.